Saturday

April 19, 2014

April 19, 2014

Posted by **Jose** on Thursday, December 1, 2011 at 11:19pm.

- Math -
**Reiny**, Thursday, December 1, 2011 at 11:46pmif the constant is missing, there is no need to use the formula, since the equation will always factor

9t^2 - 3t = 0

3t(3t-1) = 0

t = 0 or t = 1/3

if you insist ....

a = 9, b = -3, c = 0

x = (3 ± √(9-0)/18

= (3±3)/18

= 1/3 or 0

**Related Questions**

Math - The lcm for... (1+3t) (1-9t)^2 (1-3t) Answer 9t^2 or (3t+1)(-3t+1) I'm ...

College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...

math and physics - i just want to know form where i got on this formula the 4.9t...

algebra 2 - can anyone please help me solve this step by step by using the ...

math-calculus - solve equation |x^2-2x-6| using quadratic formula. i not get how...

Factoring - Factor Completely: 3t^3 + 5t^2 - 12t first take out the t so you ...

Math - Using the quadratic formula solve xsquared=2/3x Using the quadratic ...

MATH - ( 6t^2 + 2t + 1 ) 3t A) 9t^2 + 5T + 3 B) 18T^2 + 6T + 3 C) 9T^3 + 6T^3 + ...

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

Math - Use the quadratic formula to solve each of the following quadratic ...